Gambaran Prevalensi Stunting dan Praktik Pemberian ASI Eksklusif di Indonesia Berdasarkan Data SSGI 2024 - Natasia, Kiki; Rahmawati, Dinar Putri; Ardianti, Rine Dhenok (Ghidza: Jurnal Gizi dan Kesehatan, 2025)
Stunting in children is a major global public health concern, affecting approximately 155 million children worldwide and contributing to high child mortality rates, recurrent infections, and reduced opportunities for play and learning. Exclusive Breastfeeding (EBF) is a key nutritional intervention proven effective in stunting prevention. The objective of this article is to explore the prevalence of stunting and exclusive breastfeeding practices in Indonesia based on the latest available data, and to identify associated factors. This study employed a cross-sectional design using secondary data analysis based on the results of the Indonesian Nutrition Status Survey (SSGI) conducted by the Ministry of Health in 2024. The 2024 SSGI results indicate that the prevalence of stunting among toddlers in Indonesia is 19.8%, a significant decrease from 24.4% in 2022. The coverage of exclusive breastfeeding for infants aged 0-5 months reached 74.73%. However, there are variations in this figure, with the proportion among the working mother group (72.89%) being slightly lower than the non-working mother group (76.06%). Furthermore, the study identified that higher education of the Head of Household (HOH), higher household economic status, and urban residence play a significant role in reducing the prevalence of stunting in toddlers. Although stunting prevalence has decreased, EBF coverage (74.73%) remains below the government's 2024 target of 80%. Therefore, it is recommended to intensify targeted education and support programs, especially for working mothers and households with lower educational and economic status in non-urban areas, to achieve the EBF coverage target and accelerate the reduction of stunting in Indonesia.